Style Influences And JSE Sector Returns: Evidence From The South African Stock Market - Small, Wayne; Hsieh, Heng-Hsing (Journal of Applied Business Research, 2017)
A distinctive phenomenon on the Johannesburg Stock Exchange (JSE) is the market segmentation between the resource sector and the financial and industrial sectors documented in empirical literature. The dominance of the resource sector in the cap-weighted FTSE/JSE All-Share index (ALSI) implies that the ALSI index might not be mean-variance efficient due to the potential lack of diversification. We estimate and compare the historical sector exposures of the ALSI index to its hypothetically optimal sector exposures over the examination period from 2003 through 2013. It is found that to achieve mean-variance efficiency on the JSE over the examination period, one should maintain substantial investments in the industrial sector and tactically allocate the remainder of the investments to the financial sector and/or the resource sector. It is also observed that the sector exposures of the ALSI index have shifted significantly from the resource sector to the industrial sector. To gain a better understanding of the investment style influences on the JSE sector returns, we further investigate the exposures of the prominent JSE sector returns to the style risks using the Carhart (1997) four-factor model. It is found that investments in financial stocks are exposed to significant value risk and, to some degree, influenced by the performance of large caps on the JSE. In addition, excess returns on the industrial sector are attributed to value, small cap and momentum risk premiums to some degree. The performance of the resource sector, on the other hand, is mildly biased towards the growth, large cap and contrarian investment styles on the JSE.
Keywords: Johannesburg Stock Exchange (JSE); Style Anomalies; Efficient Market Hypothesis (EMH); Portfolio Optimization; Asset Pricing Models; Market Segmentation